Visión de la mujer en alumn@s de octavo grado de educación básica - Mizuno Haydar, Jorge Miguel (Íkala, Revista de Lenguaje y Cultura, 2004)
This article shows partial results of the research project "Ideology of textbooks and its influence on citizenship formation". These results deal with the role of women as presented in Social Sciences textbooks and in teachers´ discourse. Such role is studied from the discourse of eighth grade students. This article aims to analyze how ideology is expressed in both teachers´ and students´ textbooks, and how it influences citizenship formation. Data were obtained through class observations, ethnographic interviews, and text analysis by using the Functional Systemic Grammar approach. Received: 01-06-04/ Accepted: 28-09-04 How to reference this article: Mizuno Haydar, J. M. (2004). Visión de la mujer en alumn@s de octavo grado de educación básica. Íkala. 9 (1), pp. 369 – 386